PENGEMBANGAN MEDIA PEMBELAJARAN SISTEM RANGKA MANUSIA BERBASIS MULTIMEDIA INTERAKTIF DI SD NEGERI 060876 MEDAN TIMUR - Noera Sururi (JURNAL TEMATIK, 2015)
The objective of this study: (1) Developing multimedia interactive learning which can be used as a learning medium human skeletal system; (2) Knowing the students' responses regarding the quality of multimedia interactive learning as a learning medium human skeletal system; and (3) Determine student learning outcomes in human skeletal system materials using interactive multimedia in primary school of public 060876 at east medan. The subjects of this study were all students in grade five public elementary schools 060876 at east medan in the second semester of the academic year 2014/2015 amounting to 30 students. Male students were twenty one people and women amounted to thirteen people. This studi was using the quantitative approach. The mothod of this study was (research and development/R&D), Borg and Gall model. The steps that had been done were; (1) Analyze the needs and characteristics of students; (2) Formulate instructional purposes; (3) Writing and designing media manuscript media science learning; (4) Validation experts; (5) Revision; (6) Testing the final product. The result of this study showing show that (1) Test IPA subject matter experts conducted by two experts were in very good criteria (89%); (2) Test the instructional design experts conducted by two experts are in very good criteria (84%); individual testing is in very good criteria (83%); small group trial is in very good criteria (86%); field trials on the criteria very well (86%), as well as student achievement test trials using the control class and experimental class. That the learning outcomes of students who use interactive multimedia on the matter of human skeletal system is higher than the class that only use the textbook as a medium of learning.